2022
DOI: 10.3389/fenvs.2022.894779
|View full text |Cite
|
Sign up to set email alerts
|

ENSO Teleconnection to Interannual Variability in Carbon Monoxide Over the North Atlantic European Region in Spring

Abstract: Carbon monoxide (CO) is an important trace gas in the troposphere, while the El Niño-Southern Oscillation (ENSO) phenomenon is the most important tropical climate variability. ENSO is known to influence interannual variation in meteorological variables on the global scale but its influence on atmospheric CO over large areas in a long term is uncertain. Here we report a strong positive teleconnection between the El Niño–Southern Oscillation (ENSO) in winter (November to February) to tropospheric CO over the Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 133 publications
0
1
0
Order By: Relevance
“…It currently uses MERRA-2 reanalysis data as a default, which was also the case in this study. GEOS-Chem has been widely applied in atmospheric chemistry, air quality, and climate change studies [9,12,13,21,29,[35][36][37]. The GEOS-Chem's full chemistry simulation includes fully coupled O 3 -NOx-VOC-halogen-aerosol chemistry.…”
Section: Geos-chem Modelmentioning
confidence: 99%
“…It currently uses MERRA-2 reanalysis data as a default, which was also the case in this study. GEOS-Chem has been widely applied in atmospheric chemistry, air quality, and climate change studies [9,12,13,21,29,[35][36][37]. The GEOS-Chem's full chemistry simulation includes fully coupled O 3 -NOx-VOC-halogen-aerosol chemistry.…”
Section: Geos-chem Modelmentioning
confidence: 99%
“…García-Serrano et al [26] revisited the timing of the ENSO-Tropical North Atlantic relationship. Liu et al [27] reported that there exists a strong positive teleconnection between the ENSO phenomenon in the winter and the tropospheric carbon-oxide levels over the North-Atlantic European region in the follow-ing spring (March to May). Alpert et al [28] corroborate that the South Asian Monsoon plays a significant role in influencing the climate of the central and eastern Mediterranean.…”
Section: Introductionmentioning
confidence: 99%